Matrix effect management in liquid chromatography mass spectrometry: the internal standard normalized matrix effect - Nicolò, Amedeo De; Cantù, Marco; D'Avolio, Antonio (Bioanalysis, 2017)
LC-MS is becoming a standard for many applications, thanks to high sensitivity and selectivity; nevertheless, some issues are still present, particularly due to matrix effect (ME). Considering this, the use of optimal internal standards (ISs, usually stable-isotope labeled) is important, but not always possible because of cost or availability. Therefore, a deep investigation of the inter-lot variability of the ME and of the correcting power of the chosen IS (isotope-labeled or not) is mandatory. While the adoption of isotopically labeled ISs considered as a 'gold standard' to mitigate ME impact on analytical results, there is not consensus about the standard technique to evaluate it during method validation. In this paper, currently available techniques to evaluate, reduce or counterbalance ME are presented and discussed. Finally, these techniques were summarized in a flowchart for a robust management of ME, particularly considering the concept of 'internal standard normalized ME'.